Switchable multi-wavelength laser based on a core-offset Mach-Zehnder interferometer with non-zero dispersion-shifted fiber. (August 2018) - Bianchetti, M.; Sierra-Hernandez, J.M.; Mata-Chavez, R.I.; Gallegos-Arellano, E.; Estudillo-Ayala, J.M.; Jauregui-Vazquez, D.; Fernandez-Jaramillo, A.A.; Salceda-Delgado, G.; Rojas-Laguna, R.
Highlights: A switchable multi-wavelength laser. Core-offset Mach-Zehnder interferometer. Non-zero dispersion-shifted fiber. Abstract: In this paper, a switchable multi-wavelength erbium-doped fiber ring laser, based on a core-offset Mach-Zehnder interferometer (MZI) with non-zero dispersion shifted fiber (NZ-DSF), is proposed and experimentally demonstrated. Here, the core-offset MZI was implemented by fusion splicing a segment of a NZ-DSF between two single-mode fiber sections. In the proposed ring cavity design, the core-offset MZI is acting as a wavelength selective filter and it is optimized in order to achieve a single-mode suppression ratio (SMSR) of about of 56 dB. In addition, the laser is capable of emitting a single, double, or triple line, which can be switched from 1546 to 1564 nm by controlling its polarization states. Finally, this laser fiber offers a high output power stability at room temperature, compactness, robustness and low implementation cost.